Threshold preservation of PT-resonant structures in realistic-dispersive medium - Phang, Sendy; Vukovic, Ana; Creagh, Stephen C.; Benson, Trevor M.; Sewell, Phillip; Gradoni, Gabriele (2015)
The impact of material dispersion in the performance of parity-time (PT) symmetric coupled microresonators is studied. The eigenfrequencies of the coupled PT-system are analysed for different dispersion parameter. We show that realistic dispersion preserves the PT-system with additional stabilising features.